1923 Cal. Stat. 698–99, An Act to Control and Regulate the Possession, Sale and Use of Pistols, Revolvers, and Other Firearms Capable of Being Concealed Upon the Person; To Prohibit the Manufacture, Sale, Possession or Carrying of Certain Other Dangerous Weapons Within this State; To Provide for Registering All Sales of Pistols, Revolvers or Other Firearms Capable of Being Concealed Upon the Person; To Prohibit the Carrying of Concealed Firearms Except by Lawfully Authorized Persons; To Provide for the Confiscation and Destruction of Such Weapons in Certain Cases; To Prohibit the Ownership, Use or Possession of Any of Such Weapons by Certain Classes of Persons; To Prescribe Penalties for Violations of This Act and Increased Penalties for Repeated Violations Hereof; To Authorize, In Proper Cases, The Granting of Licenses or Permits to Carry Firearms Concealed Upon the Person; To Provide for Licensing Retail Dealers in Such Firearms and Regulating Sales Thereunder; And To Repeal Chapter One Hundred Forty-Five of California Statutes of 1917, ch. 339, § 8 - (:unkn) unknown (General Publisher, 1923)
Allowed the Sheriff or the county and the board of police commissioners, chief of police, town martial, or other police department to reqire proof of good moral character for the issuane of a license for a concealed pistol, revolver, or other firearm for a period of one year.
--
Keywords: PEACE OFFICERS